The Clot Thickens: Diagnosing Acute Pulmonary Embolism as a Trigger for Chronic Obstructive Pulmonary Disease Exacerbation in the Setting of Anticoagulation Failure - Saleh, Sameh N (Eur J Case Rep Intern Med, 2020)
Chronic obstructive pulmonary disease (COPD) exacerbations are most commonly triggered by infections, but up to 25% of those that require hospitalization are thought to be triggered by acute pulmonary embolism. We present the case of a 71-year-old patient with a history of unprovoked pulmonary embolisms on anticoagulation therapy hospitalized for a COPD exacerbation. The exacerbation was triggered by an acute pulmonary embolism, representing anticoagulation failure. LEARNING POINTS: Pulmonary embolism (PE) is an important trigger of COPD exacerbations and should be considered, especially when there is an unexplained abrupt or recurrent increase in the frequency or severity of exacerbations. Therapeutic anticoagulation does not preclude the presence of PE. Clinical risk stratification is a crucial component of medical decision-making.